2019
DOI: 10.1039/c9dt00601j
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobicity may enhance membrane affinity and anti-cancer effects of Schiff base vanadium(v) catecholate complexes

Abstract: Hydrophobicity may increase the hydrolytic stability of vanadium(v) catecholate complexes enabling rapid cellular uptake of the intact complex exhibiting potent anti-cancer activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
104
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 54 publications
(113 citation statements)
references
References 94 publications
8
104
1
Order By: Relevance
“…fetal calf serum, pH 7.4) [5d] at 310 K (t1 = 2 % 30 s), as shown by electronic absorption spectroscopy ( Figure S1, Supporting Information), while further redox and ligandexchange reactions of the released V V species with the medium were expected to take up to 24 h to complete. [11,12] Preliminary assays using human bone cancer cells [11] showed that 1 at 5.0 mm concentration lost most of its toxicity after pre-incubation with cell culture medium for 24 h at 310 K and 5 % CO 2 .…”
mentioning
confidence: 99%
“…fetal calf serum, pH 7.4) [5d] at 310 K (t1 = 2 % 30 s), as shown by electronic absorption spectroscopy ( Figure S1, Supporting Information), while further redox and ligandexchange reactions of the released V V species with the medium were expected to take up to 24 h to complete. [11,12] Preliminary assays using human bone cancer cells [11] showed that 1 at 5.0 mm concentration lost most of its toxicity after pre-incubation with cell culture medium for 24 h at 310 K and 5 % CO 2 .…”
mentioning
confidence: 99%
“…Complexes 1 – 7 retained dimeric structures under biomimetic conditions (50 μ m Ru, 10 m m aqueous NH 4 HCO 3 , pH 7.5, stored for up to a week at 295 K), as shown by ESI‐MS (Figure S8). These results contrast those for typical metal complexes that rapidly decompose under cell culture conditions . Stock solutions of 1 – 7 used in the ESI‐MS studies (2–20 m m Ru in DMF) were stored for about a month in the dark at 295 K prior to the dilution with 10 m m NH 4 HCO 3 .…”
Section: Resultsmentioning
confidence: 90%
“…Preliminary studies compared the effects of 1 – 7 (10–100 μ m Ru, 72–96 h) on the proliferation rates of two contrasting human cancer cell lines: 1) MDA‐MB‐231 (breast cancer, mesenchymal‐like, highly invasive) and 2) A549 (lung cancer, epithelial, noninvasive in the absence of growth factor stimulation), using real‐time observations with IncuCyte Zoom imaging system . Typical results (Figures S6 and S7) indicated that only 2 a , b and 5 (i.e., the complexes that contained phenyl groups in the ligands, Schemes and ) had promising antiproliferative activities at ≈50 μ m Ru.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations